2022
DOI: 10.21203/rs.3.rs-1799738/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immunodominance of epitopes and protection efficacy of RBD antigen are differentially altered by different adjuvants and immune pathways

Abstract: Purpose Previous studies have revealed that the receptor-binding domain (RBD) of the spike protein is immunogenic in both mice and healthy volunteers, and the humoral immune response plays key roles in RBD-mediated protection. In this study, we evaluated the immunodominant humoral response of RBD with different adjuvants and different immune routes in inducing neutralizing antibodies and immunodominant epitopes in RBD. Methods In this study, we investigated the protective efficacy of immunization with RBD pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…These epitopes notably contained immunodominant peptide sequences, “VRQIAP” and “YQAGSTP,” pivotal for eliciting the humoral immune response. Moreover, our work uncovered additional immunodominant epitopes, “VLYNSASFSTFKYGVSP” and “PFERISTEIYQAGSTPC,” reportedly influential in IgG response stimulation in BALB/c mice [23] .…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…These epitopes notably contained immunodominant peptide sequences, “VRQIAP” and “YQAGSTP,” pivotal for eliciting the humoral immune response. Moreover, our work uncovered additional immunodominant epitopes, “VLYNSASFSTFKYGVSP” and “PFERISTEIYQAGSTPC,” reportedly influential in IgG response stimulation in BALB/c mice [23] .…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, we conducted an in silico study of rRBD epitopes against B cell receptors using immunoinformatic prediction Bepipred 2.0 on https://tools.iedb.org , seven of which could bind antibodies ( Figure S2 ). Jiang et al [22] and Li et al [23] demonstrated that the SARS-CoV-2 RBD epitopes “ATRFAS,” “YAWNRKRISN,” “DEVRQIAPGQTGKIADYNYK,” “STEIYQAGSTPCNGVE” [22] , as well as “VLYNSASFSTFKYGVSP” and “PFERISTEIYQAGSTPC” [23] are dominant and bind immunoglobulins (Ig).…”
Section: Resultsmentioning
confidence: 99%